2019
DOI: 10.1038/s41598-019-50754-4
|View full text |Cite
|
Sign up to set email alerts
|

Realizing High Thermoelectric Performance at Ambient Temperature by Ternary Alloying in Polycrystalline Si1-x-yGexSny Thin Films with Boron Ion Implantation

Abstract: The interest in thermoelectrics (TE) for an electrical output power by converting any kind of heat has flourished in recent years, but questions about the efficiency at the ambient temperature and safety remain unanswered. With the possibility of integration in the technology of semiconductors based on silicon, highly harvested power density, abundant on earth, nontoxicity, and cost-efficiency, Si1-x-yGexSny ternary alloy film has been investigated to highlight its efficiency through ion implantation and high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 41 publications
(40 reference statements)
0
34
0
Order By: Relevance
“…We previously reported precipitation of Sn particles in SiGeSn films can significantly improve the carrier concentration and mobility, thus greatly enhancing the TE performance under room temperature. [ 38 ] In this work, we measured the Hall mobility and carrier concentration of the samples at room temperature to examine the effect of Sn particles on the electron‐transport property. In Figure 4 a, the carrier concentrations of all samples were higher than the designed value (4 × 10 20 cm −3 ) while the mobilities of all the samples were almost similar.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported precipitation of Sn particles in SiGeSn films can significantly improve the carrier concentration and mobility, thus greatly enhancing the TE performance under room temperature. [ 38 ] In this work, we measured the Hall mobility and carrier concentration of the samples at room temperature to examine the effect of Sn particles on the electron‐transport property. In Figure 4 a, the carrier concentrations of all samples were higher than the designed value (4 × 10 20 cm −3 ) while the mobilities of all the samples were almost similar.…”
Section: Resultsmentioning
confidence: 99%
“…3 Figure 4a plots the temperature-dependent n of the samples TiZr x NiSn (x = 0, 0.005, 0.015, 0.025), which shows a decrease trend with the increase of Zr content. It is demonstrated that the impurity of residul elemental Sn could increase the n in TiNiSn [15,31].Conversely, the residual Sn in TiNiSn is diminished with the increase of Zr content (Fig. 1b), which could contribute a decrease in the n.…”
Section: Resultsmentioning
confidence: 93%
“…SiGe-based alloys are a promising material for thermoelectric devices such as a micro-energy generator for wearable and portable electronics (Peng et al, 2019;Francioso et al, 2011). SiGe compounds have the advantage of being widely available, inexpensive, and non-toxic.…”
Section: Introductionmentioning
confidence: 99%